ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI LUAS PENGUNGKAPAN INFORMASI SUKARELA LAPORAN TAHUNAN (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2008-2010) - Anita Yolanda Suta; Herry Laksito (Diponegoro Journal of Accounting, 2012)
The aims of this study is to analyze the influence of firm characteristics on voluntary disclosure inannual report in Indonesia. Factors tested in this study are firm size, firm age, leverage,ownership dispersion, net profit margin, return on equity, liquidity, and proportion of independentboard of commissioners. Collecting data is using porposive sampling methode to themanufacturing companies that listed in Indonesian Stock Exchange during 2008-2010. This studyuses content analysis to measure the extent of voluntary disclosure. There are 103 voluntarydisclosure items to detect the extent of voluntary disclosure. This study used agency theory,stakeholder theory, and signal theory to explain lingkage between variables. This research usesmultiple regression that use to examine the influence of firm characteristics on voluntarydisclosure in annual report. The result of this research showed those independent variables thathave significant influence on extent of voluntary disclosure is firm size, leverage, and liquidity.However, firm age, ownership dispersion, net profit margin, return on equity, and proportion ofindependent board of commissioners do not show significant influence on the extent of voluntarydisclosures.